The city besieged : siege and its manifestations in the ancient Near East - Ephʻal, Israel. (Culture and History of the Ancient Near East, 2009)
Exploring the military, legal, social and literary aspects of ancient warfare, this study examines the multifaceted nature of the siege phenomenon in the Ancient Near East. The book is based on Akkadian and biblical (and, to lesser degree, Greek, Aramaic, Egyptian, Hittite and Ugaritic) sources as well as on the depictions on reliefs from Assyrian palaces and Egyptian temples. The analysis incorporates lexical study and military thinking and focuses on the technology of warfare and human behavior in a state of emergency. This volume is a co-publication between Brill and The Hebrew University Magnes Press. \'...this book serves as an excellent overview of siege practices and their result as seen from the biblical and Mesopotamian perspective.\' Michael G. Hasel, Institute of Archaeology-Southern Adventist University